1993
DOI: 10.1159/000284802
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Smoking Habits and Attitudes of Patients and Staff in Psychiatric Hospitals

Abstract: One hundred and six staff members and 150 patients of three psychiatric hospitals in Israel were administered a smoking habit and attitutes questionnaire. Upon analyzing the data, staff members and patients made up a very high percentage of smokers, 48.1 and 76%, respectively. The staff was not knowledgeable enough about the hazards of smoking. Nurses generously used cigarettes in order to appease the patients. Furthermore, the patients admitted being encouraged to smoke by the staff. According to these findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
2
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
1
17
2
4
Order By: Relevance
“…This probably reflects the variable roles and practical challenges faced by different professionals within a multidisciplinary setting. Similar observations were noted in previous studies where professionals differed in their views on benefits in staff smoking with service users (Mester et al, 1993;Tarbuck, 1996).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This probably reflects the variable roles and practical challenges faced by different professionals within a multidisciplinary setting. Similar observations were noted in previous studies where professionals differed in their views on benefits in staff smoking with service users (Mester et al, 1993;Tarbuck, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…This study reports a smoking rate of 23.1% among mental healthcare staff and 46.4% of respondents who had smoked at least once, which is less than in previous studies (Gubbay 1992;Mester et al, 1993). There were more smokers among female staff (27%) than among male staff (19%), but the overall number of smokers decreased with increasing age group.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…One study found that psychiatric nurses had a smoking prevalence rate twice that of other nurses (Gubbay, 1992). An Israeli study reported higher rates of smoking among psychiatric unit staff than in the general population (Mester et al, 1993). Less than 5% of British doctors now smoke, although separate figures for psychiatrists are not available.…”
Section: Discussionmentioning
confidence: 99%